Enriching user stories with usability features in a remote agile project: a case study - Marques, Anna Beatriz; Costa, Alex Felipe; Santos, Ismayle; Andrade, Rossana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Considering usability aspects in the early phases of software development can avoid rework to solve usability problems identified late. We can adopt Requirements Engineering methods to identify usability requirements that explore the end users’ perspectives and usage preferences. However, usability evaluation methods are more commonly adopted in the industry than early usability methods to define usability requirements. Recently, the USARP method was proposed for usability requirements elicitation and specification. USARP suggests the combined use of personas, user stories, and usability guidelines. This paper aims to report a case study on the USARP adoption by a remote agile team in the industry. USARP supports the team in defining UI/UX requirements for a web management tool. A survey enables us to investigate the teams’ perception of the usefulness of the USARP. The results showed that USARP improved the team’s effectiveness in usability requirements elicitation. USARP enabled identifying 120 UI/UX aspects related to system functionalities. We expect this experience report can contribute to disseminating early usability methods in industry practice.